THE ENERGY-SAVING TECHNOLOGIES USE ACTIVATION IN CROPS - A GUARANTEE OF EFFECTIVE DEVELOPMENT OF THE ENTERPRISES ECONOMY IN UKRAINE (INNOVATIVE ECONOMY, 2021)
Parkhomets M.K., Uniiat L.M., Chorna N.P. THE ENERGY-SAVING TECHNOLOGIES USE ACTIVATION IN CROPS - A GUARANTEE OF EFFECTIVE DEVELOPMENT OF THE ENTERPRISES ECONOMY IN UKRAINEPurpose. The aim of the article is conduction of a retrospective analysis of the experience results of introducing innovative, energy-saving technologies in agriculture of Ukrainian enterprises.Choosing of inhibitory factors of innovative development and providing recommendations for further introduction of innovations to increase economic efficiency and competitiveness of agricultural enterprises in different regions of our country.Methodology of research. The following research methods were used to achieve this goal: monographic – for a detailed study of phenomena, processes and best practices of enterprises; abstract and logical - to outline the main factors influencing the accelerated use of energy-saving, innovative technologies in agriculture of Ukrainian enterprises; for the description of analytical tables, formation of conclusions and offers; comparative analysis - to compare the effectiveness of the different variants of technologies used for growing crops in crop rotations.Findings. Energy-saving, innovative technologies in agriculture by crop rotations in the regions of Ukraine are generalized and systematized. It is recommended for the Left-Coast Forest-Steppe and Steppe to use a differentiated system of tillage in crop rotations, which reduces about 120-150 UAH / ha of direct costs compared to traditional plowing.Originality. The substantiation of introduction of energy saving technologies in agriculture on crop rotations and their effective influence on development of the enterprises economy in separate regions of Ukraine has received further development.Practical value. Substantiated results of the study can be used by agricultural enterprises, which will increase the economic efficiency of both the crop sector and promote the development of the agricultural economy in the regions of Ukraine.Key words: energy-saving technologies in agriculture, “Mini-till”, “No-till”, “Strip-till”, differentiated technologies, resource savings, productivity, economic efficiency, competitiveness.
Keywords: Key words; energy-saving technologies in agriculture; “Mini-till”; “No-till”; “Strip-till”; differentiated technologies; resource savings; productivity; economic efficiency; competitiveness.